1984
DOI: 10.1159/000284129
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine and α<sub>1</sub>-Adrenergic Sensitivity in the Separation of Depression and Anxiety

Abstract: Three relatively clear-cut diagnostic groups, namely primary major depressive disorder-endogenous subtype (PRI MDD-E), primary anxiety disorder with no depression (PRI ANX), and normal controls as well as two additional patient groups with mixed or coexisting anxious/depressive diagnoses were studied. Clinical assessment was made by routine psychiatric interview, Schedule of Affective Disorder and Schizophrenia (SADS) research interview, and obtaining family history of MDD. Subjects underwent both routine ‘bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
2

Year Published

1986
1986
1997
1997

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
18
0
2
Order By: Relevance
“…Akiskal et al [ 17] also described difficulties initiating and maintaining sleep in a mixed sample of anxious patients including some patients with G A D or panic attacks. The latter was also described by Sitaram et al [18].…”
Section: Discussionsupporting
confidence: 53%
“…Akiskal et al [ 17] also described difficulties initiating and maintaining sleep in a mixed sample of anxious patients including some patients with G A D or panic attacks. The latter was also described by Sitaram et al [18].…”
Section: Discussionsupporting
confidence: 53%
“…Further studies in identical twins suggested that the response on the CRIT might be partially under genetic control (131). Since the original study, Sitaram and his colleagues have confirmed the general cholinergic muscarinic supersensitivity in patients with endogenous depres sion using the CRIT (132)(133)(134). Our own recent preliminary results confirm a faster REM induction in patients with major depressive disorder and bipolar depression with an arecoline dose of 1.0 mg than with a 0.5-mg dose.…”
Section: Summary Of Basic Mechanismsmentioning
confidence: 59%
“…Akiskal et al [16] also described difficulties initiating and maintaining sleep in a mixed sample of anxious patients including some with general ized anxiety or panic attacks. The latter was also de scribed by Sitaram et al [17], As far as sleep architecture is concerned, Papadimi triou et al [18] observed a decreased stage 2 in their hos pitalized GAD patients, as compared with controls, Lauer et al [59] an increased stage 1. These data are in agree ment with our present findings.…”
Section: Discussionmentioning
confidence: 72%